Лекарственные растения: справочник / И. А. Губанов - Губанов Иван Алексеевич (МГУ, 1993)
Экземпляры: ф.12 (1999) / Инвентарный номер: 41010 / Цена: / Сис.шифр: 42.143 / Авт.знак: Г 93 / ГРНТИ: 68.35.43 / ББК: 53.525я2